Diversity of cowpea (Vigna unguiculata (L.) Walp) landraces in Mozambique: new opportunities for crop improvement and future breeding programs - Gomes, Ana Maria Figueira (2021)
Cowpea (Vigna unguiculata) is a neglected crop native to Africa, with an outstanding potential to contribute to the major challenges in food and nutrition security, as well as in agricultural sustainability. Two major issues regarding cowpea research have been highlighted in recent years—the establishment of core collections and the characterization of landraces—as crucial to the implementation of environmentally resilient and nutrition-sensitive production systems. In this work, we have collected, mapped, and characterized the morphological attributes of 61 cowpea genotypes, from 10 landraces spanning across six agro-ecological zones and three provinces in Mozambique. Our results reveal that local landraces retain a high level of morphological diversity without a specific geographical pattern, suggesting the existence of gene flow. Nevertheless, accessions from one landrace, i.e., Maringué, seem to be the most promising in terms of yield and nutrition-related parameters, and could therefore be integrated into the ongoing conservation and breeding efforts in the region towards the production of elite varieties of cowpea